PENGARUH LATIHAN MENGGUNAKAN MEDIA TARGET TERHADAP KETEPATAN HASIL SHOOTING SEPAKBOLA - Prasetyo, Bimo; Triansyah, Andika; Haetami, Mimi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract This research aims to determine the effect of target media modification on the accuracy of football shooting results, using an experimental method with the design of